VMware vSphere 4 implementation [ - Laverick, Mike (McGraw-Hill, 2010)
"Design and deploy a high-performance cloud-based enterprise IT platform with guidance from a VMware expert.Featuring tips, techniques, and best practices, VMware vSphere 4 Implementation explains how to dramatically cut hardware costs, maximize computing power, and centralize system administration. Configure hardware and storage devices, build virtual machines and networks, install guest operating systems, and import physical machines. Security, disaster recovery, performance tuning, and system updates are also covered in this comprehensive resource"--Resource description p